Reversal of H-bonding direction by N-sulfonation in a synthetic reverse-turn peptide motif - Vijayadas, Kuruppanthara N.; Kotmale, Amol S.; Thorat, Shridhar H.; Gonnade, Rajesh G.; Nair, Roshna V.; Rajamohanan, Pattuparambil R.; Sanjayan, Gangadhar J. (Organic & Biomolecular Chemistry, 2015)
This communication depicts an intriguing example of hydrogen-bonding reversal upon introduction of a sulfonamide linkage at the N-terminus of a synthetic reverse-turn peptide motif. The ready availability of two sulfonyl oxygen atoms, as hydrogen-bonding acceptors, combined with the inherent twisted conformation of sulfonamides are seen to act as switches that engage/disengage the hydrogen-bond at the sticky ends/termini.

Role of N-terminal proline in stabilizing the Ant-Pro zipper motif - Kheria, Sanjeev; Nair, Roshna V.; Kotmale, Amol S.; Rajamohanan, Pattuparambil R.; Sanjayan, Gangadhar J. (New Journal of Chemistry, 2015)
Hetero-chiral hybrid peptides of the general sequence (L)alpha beta(D)(n)alpha beta(n) featuring proline (Pro, a constrained alpha-amino acid) and anthranilic acid (Ant, a constrained beta-amino acid) as building blocks, where n = 2, 4 etc., form a three-dimensional zipper-like architecture. These zipper peptides attain stable conformation by balancing the co-operative contribution of two competing non-covalent forces, namely hydrogen bonding and aromatic stacking. However, the selection of the N-terminal residue also stands to be one of the key contributors in stabilising the unusually long-range intramolecular hydrogen bond, featuring 26 atoms in the H-bonded ring observed at the termini. This article deals with the substitution alterations at the N-terminus of the zipper motif and their consequent influences on its structure and stability. In this study, the N-terminal Pro residue of the zipper motif was substituted with a flexible amino acid, alanine, and a constrained acyclic amino acid, 2-aminoisobutyric acid, to investigate the role of N-terminal proline in stabilizing the Ant-Pro zipper motif, and its stabilities were assessed by employing solution-state NMR and restrained MD simulation studies.

Residue dependent hydrogen-bonding preferences in orthanilic acid-based short peptide beta-turn motifs - Jedhe, Ganesh S.; Vijayadas, Kuruppanthara N.; Kotmale, Amol S.; Sangtani, Ekta; Shinde, Dinesh R.; Gonnade, Rajesh G.; Rajamohanan, Pattuparambil R.; Sanjayan, Gangadhar J. (RSC Advances, 2016)
This communication describes the competition between native beta-turn (C10) and 2-aminobenzenesulfonic acid (SAnt)( orthanilic acid)-based pseudo beta-turn (C11) in their hybrid peptides. Solid-state crystal structure and solution-state NMR studies revealed that C10 and C11 can be simultaneously observed under appropriate conditions. The variable temperature NMR coefficient data suggest that the isolated C11/C14 hydrogen bond is weaker in comparison with the consecutive C10 and C11 turns.

Reactivity of difunctional polar monomers and ethylene copolymerization: a comprehensive account - Gaikwad, Shahaji R.; Deshmukh, Satej S.; Koshti, Vijay S.; Poddar, Suparna; Gonnade, Rajesh G.; Rajamohanan, Pattuparambil R.; Chikkali, Samir H. (Macromolecules, 2017)
A comprehensive picture of insertion of 1,1-disubstituted difunctional olefins, their ability to double the functional group density at the same level of incorporation as that of monofunctional olefin, and copolymerization with ethylene has been demonstrated. Exposure of a palladium complex [P boolean AND OPdMe(L)] (P boolean AND O = kappa(2)-P,O-Ar2PC6H4SO2O with Ar = 2-MeOC6H4.; L = C2H6OS) to methyl 2-acetamidoacrylate (MAAA) revealed slight preference for 1,2-insertion over 2,1-insertion (1.0:0.7). In contrast, insertion of electron-deficient 2-(trifluoromethyl)acrylic acid (TFMAA) unveiled selective 2,1-insertion {via [(P boolean AND O)PdC5H6F3O2] (11)1. The unstable intermediate 11 undergoes beta-hydride and beta-fluoride elimination to produce subsequent insertion and elimination products. The identity of elimination products (E/Z)-2-trifluoromethyl)but-2-enoic acid [17(E/Z)] and 2-(difluoromethylene)butanoic acid (13) was fully established by 1-2D NMR spectroscopy. These insertion experiments, taken together with insertion rates, suggest that MAAA and TFMAA. are amenable to insertion. Polymerization of ethylene with MAAA, TFMAA, acetamidoacrylic acid, 2-bromoacrylic acid, dimethyl allylmalonate, and allylmalonic acid was catalyzed by [P boolean AND OPdMe(L)] (L = C2H3N) (S.ACN), and the highest incorporation of 11.8% was observed for dimethyl allylmalonate (DMAM). The changes in the surface properties of the copolymers after incorporation of difunctional olefins were evaluated by measuring the water contact angle. Copolymer with highest (11.8% of DMAM) incorporation revealed a reduced water contact angle of 76 degrees. These findings demonstrate that 1,1-disubstituted difunctional olefins are amenable to polymerization, and incorporation of difunctional olefins In polyethylene backbone leads to the production of relatively hydrophilic polyethylene copolymers.